THE IMPACT OF COST OF DEBT, INVENTORY INTENSITY AND PROFITABILITY TOWARD TAX AVOIDANCE ON NON-CYCLICALS CONSUMER GOODS COMPANIES LISTED ON THE IDX - Tarigan, Louis Yosen Primsa; Fortuna, Felicia (Jurnal Penelitian Akuntansi (JPA), 2025)
This research is conducted to determine the impact of the cost of debt, inventory intensity, and profitability toward tax avoidance. It observes non-cyclicals consumer goods companies listed on the Indonesia Stock Exchange in 2021 and 2022. There are 57 non-cyclicals consumer goods companies, from which 29 companies fulfill the criteria. For two years observation, total sample for the research is 58 units. The research used secondary data from the Indonesia Stock Exchange with purposive sampling method. The data collected for the research will be analyzed using classical assumption test and multiple linear regression analysis method. The analysis tool used is SPSS version 26. The result of this research show that cost of debt, inventory intensity, and profitability simultaneously do not significantly influence the tax avoidance. Meanwhile, the cost of debt is partially significant toward tax avoidance with significance value of 0.015 while the inventory intensity and profitability are partially insignificant toward tax avoidance in non-cyclical consumer good companies that are listed on the Indonesia Stock Exchange for Year 2021-2022.